Produktivitas Primer Danau Lait Kecamatan Tayan Hilir Ditinjau dari Kelimpahan dan Kandungan Klorofil-a Fitoplankton - Mukarlina1, Natalia Manurung, Tri Rima Setyawati1 (Universitas Tanjungpura, 2015)
The phytoplankton is one of the producers on waters that have capability of photosynthesis and can be used to determine the level of the primary productivity on waters. This research aims to determine the primary productivity and the fertility level of the Lait Lake based on the abundance and content of phytoplankton chlorophyll-a. In this research, the method used was purposive sampling and the data analysis used was Pearson correlation. The results of the research found 48 genera of phytoplankton comprises 33 genera of Chlorophyta, 8 genera of Chrysophyta, 3 genera of Euglenophyta, 3 genera of Cyanophyta, and 1 genera of Phyrrophyta. The Phytoplankton of the Chrysophyta division has the highest abundance (1957.44 ind / L), but the quantity of genera found was fewer. The abundance of phytoplankton on waters Lait Lake ranged from 998.40 to 6609.29 ind/L with chlorophyll-a ranged from 0.05 to 0.20 mg/m3, and therefore the Lait Lake categorized as water with low fertility level (oligotrophic).